Aspirations to become a sharia accountant: A multigroup analysis between Islamic and public university - Muamar Nur Kholid; Yunice Karina Tumewang; Hanudin Amin (Faculty of Economics, Universitas Islam Indonesia, 2022)
Purpose – Using Social Cognitive Career Theory (SCCT), this study tries to find out what factors influence accounting students' intention to be-come Sha¬ria Accountants. This research also investigates the university envoronment’s moderating effect (Islamic-Based University vs Public University).Methodology – The participants in this study were chosen using a purposive sampling method from undergraduate accounting students in Yogyakarta who had completed Shariah accounting or related courses. A total of 231 people took part in this study. SmartPLS 3.0 was used to conduct the multigroup analysis in this study.Findings – The results of this study indicate that self-efficacy and outcome expectations have a significant and positive effect on the intention of accounting students to become Shariah Accountants. In addition to that, the influence of self-efficacy on intention is moderated by the university environment, in which the role of self-efficacy becomes more important for students from Islamic-based universities than those from public universitiesImplications – This research is useful for universities majoring in accounting to support accounting students to become sharia accountants. Islamic-based universities and public universities need to improve knowledge and skills of Islamic accounting and finance to increase students' self-efficacy regarding Islamic accounting. Lecturers need to convey information to students about the various benefits obtained by sharia accountants to encourage students to become sharia accountants.Originality – This study contributes to the growing empirical literature on accounting education. This article offers the importance of considering the university environment in the SCCT framework to understand the intentions of accounting students to become sharia accountants.